On Priming Medical Students in Medical Informatics - Möhr, J. R.; Sawinski, R. (Methods of Information in Medicine, 1985)
An introductory course in medical informatics (MI) for medical students in their second year of clinical education is described with respect to structure, contents and results. A positive effect was considered to have been obtained by offering a motivating course, comprising modest amounts of theory and practice and consisting of only four lectures of ninety minutes duration. The approach is discussed as an alternative to an attempt to provide a thorough theoretical basis for medical informatics to medical students in the current curricular context.
Keywords: Medical Education; Medical Informatics Education; Federal Republic of Germany; Didactics of Medical Informatics